Reading the Bible Latinamente : Latino/a interpretation for the life of the church - Padilla DeBorst, Ruth.; Carroll R., M. Daniel; Echevarria, Miguel G., (Michael Martin Chester) (Baker Academic; Grand Rapids, Michigan, 2024)
"Drawing on their diverse backgrounds and experiences, three influential scholars bring their expertise in Old Testament, New Testament, theology, and missiology to bear on the topic of biblical interpretation"--
"The doctrine of deification or theosis has been gaining interest among scholars for some time. Yet most publications on the topic have focused on Orthodox and Roman Catholic traditions and have subsumed the discussion under the category of soteriology. If "being transformed into the same image" (2 Corinthians 3:18) is truly essential to the Christian life, a fuller understanding of this biblical concept is needed for Christians of all traditions.In this volume, biblical scholars and theologians offer a constructive account of deification that breaks new ground in key ways. First, several essays focus on the work of major Protestant thinkers and Protestant expressions of the doctrine-including Lutheran, Reformed, Baptist, Wesleyan, Pentecostal, and Evangelical. Second, contributors incorporate deification into arenas that have thus far remained largely unexplored, such as the relationship between justification and deification, applications for theological education, how deification compares with transhumanism, the impact of translation philosophy on the visibility of deification in Scripture, and perspectives on deification in global Christianity.Contributors include both senior and younger scholars from a variety of backgrounds, including Alister McGrath, Ann Jervis, Veli-Matti Ka||rkka||inen, Ben C. Blackwell, and Michael Gorman. Transformed into the Same Image invites readers to dive deeper into the doctrine of deification and continue the conversation"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Hermeneutics